Extraction and Chemical Compounds Identification of Red Rice Bran Oil Using Gas Chromatography – Mass Spectrometry (GC-MS) Method - Hoo Sheren Hartono; Hartati Soetjipto; A. Ign. Kristijanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2017)
The objectives of the study are to obtain optimum yield of extraction red rice bran oil, to determine the physico-chemical characteristics, and componen coumpounds. Data was analyzed using Nir Parametric Statistics by Friedmann test. The result showed the optimum extraction results was obtained by the ratio of substrate : solvent of 1: 8 and the oil yield was 12.31 ±0.325%. The physico properties of red rice bran oil were greenish brown colour, with a density ranged from 0.908 ± 0.014 to 0.922 ± 0.014 (g/mL), and the water content ranged from 0.87 ± 0.06 to 0.91 ± 0.02 %. The chemical properties of red rice bran oil were: the acid number ranged from 116.41 ± 1.22 to 118.11 ± 2.45 (mg NaOH/g); the saponification number ranged from 193.74 ±21.88 to 199.62 ± 12.63 (mg KOH/g); and the peroxide number ranged from 24.37 ± 2.44 to 26.07 ± 4.88 (mgek/kg), respectively. Oils was analyzed used GC-MS. The chemical components of rice bran oil are oleic acid (46.24%), palmitic acid (18.25%), linoleic acid (13.29%), 9-octadecane(7.76%).